Circadian blood pressure profile and blood pressure changes following oral appliance therapy for obstructive sleep apnoea. Issue 11 (November 2021) - Sutherland, Kate; Dissanayake, Hasthi U.; Trzepizur, Wojciech; Gagnadoux, Frederic; Cistulli, Peter A.
Abstract : Objectives: Oral appliance therapy for obstructive sleep apnoea (OSA) reduces blood pressure (BP) but there is little information on relationship to circadian BP pattern (nocturnal BP dipping or non-dipping). The aims of this study were to determine whether nocturnal dipping pattern influences BP changes following oral appliance therapy, and to determine the effect of oral appliance therapy on circadian BP pattern. Methods: Participants in two randomized trials of oral appliance therapy (1–2 months) with 24-h ambulatory BP monitoring (ABPM) data were included ( N  = 152). Nocturnal BP Dippers (nocturnal/diurnal SBP ratio <0.9) and non-dippers were compared for BP changes following oral appliance therapy and the effect of oral appliance therapy on nocturnal BP dipping was assessed. Results: Of 152 participants, 64.5% were dippers. Dippers were on average younger and less likely to be hypertensive (42 vs. 82.7%, P  < 0.001). Nondippers showed greater reduction in nocturnal BP measures, related to higher BP measures at baseline. There was no difference in the relationship between treatment effectiveness and BP changes between groups. Oral appliance therapy converted only 23% of baseline non-dippers to a nocturnal dipping profile. Conclusion: Baseline circadian BP profile influenced the BP response to oral appliance therapy, largely because of higher baseline BP in the non-dipper subgroup. Oral appliance therapy did not convert OSA patients to a more favourable circadian BP profile. Further work is required to understand the effect of oral appliance therapy on circadian BP profile and of the individuals who will receive cardiovascular benefit from oral appliance therapy.